Symptoms of mania and anxiety do not contribute to suicidal ideation or behavior in the presence of bipolar depression. (January 2022) - Persons, Jane E.; Lodder, Paul; Coryell, William H.; Nurnberger, John I.; Fiedorowicz, Jess G.
Highlights: There was no increased risk of suicidal ideation or behavior attributable to manic and anxiety symptom clusters. A small amount of risk was attributable to severe depressive symptoms. Future studies should include larger samples and more rigorous assessments. Abstract: Bipolar disorder is typified by episodes of manic/hypomanic and depressive symptoms, either distinctly or concurrently as mixed symptoms. While depressive symptoms are the major driver of risk, it is unclear whether specific combinations of manic and anxiety symptoms contribute differentially to suicidal ideation and behavior in individuals with bipolar disorder during a depressive state. This study uses a quantitative application of Rothman's theoretical framework of causation, or 'causal pies' model. Data were obtained from the National Network of Depression Centers Mood Outcomes Program for 1028 visits from 626 individuals with bipolar disorder with current moderate-to-severe depressive symptoms, operationalized as a Patient Health Questionnaire-8 (PHQ-8) score ≥10. Mania symptoms were captured using the Altman Self-Rating Mania scale (ASRM) and anxiety symptoms were captured using the Generalized Anxiety Disorder-7 scale (GAD-7). The outcome of suicidal ideation or behavior was captured using the Columbia Suicide Severity Rating Scale (C-SSRS). In this cohort of individuals with bipolar disorder and at least moderate depressive symptoms, we found no increased risk of suicidal ideation or behavior attributable to manic and anxiety symptom clusters in individuals with bipolar disorder during depressive state. A small amount (4%) of risk was attributable to having severe depressive symptoms. These findings, however, may be influenced by limitations in sample size and measurement instruments. Future studies would benefit from larger samples and more rigorous assessments, including clinician-rated measures.